Distribution of personal wealth in Ireland - evidence reexamined - Chesher, Andrew D.; McMahon, Patrick C. (Economic & Social Studies, 1976)
In a recent article in this journal, Harrison and Nolan (1976) question the assumption made by Lyons (1975) that the estates of Irish adults dying in 1966 which were not examined by the Estate Duty Branch of the Revenue Commissioners of Ireland had zero net value. Lyons uses this assumption when estimating the inequality of the Irish wealth distribution. The primary purpose of this note is to draw attention to some fallacies in the argument of Harrison and Nolan. A secondary objective is to present a new estimate o f the net value of unexamined estates.
Keywords: Personal wealth; Estates